2022
DOI: 10.1111/ffe.13714
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion fatigue of Ti‐6Al‐4V coupons manufactured by directed energy deposition

Abstract: Titanium is a versatile biocompatible metal that is desirable in additively manufactured medical implant devices. However, additively manufactured parts have particular microstructures, porosity, residual stress, and surface conditions which can have a strong impact on fatigue performance. Implants have an added complexity from the saline operating environment and the associated impact on the safe design life. Equally, direct energy deposition induces a complex thermal history which, if not carefully controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…14 This synergy may expedite the crack initiation and accelerate the fatigue crack propagation under localized corrosive effects. 13 In this regard, while extensive studies have been conducted on corrosion fatigue and its impact on the fatigue life of titanium alloys, 4,15 there is a paucity of research on porous structure implants with varying porosity gradients reported thus far. Therefore, considering the potential impact of variations in porosity gradients and corrosive solutions on the fatigue properties of alloys, and with the aim of comparing the fatigue characteristics of different gradient structures in a human body environment, the goal is to identify porous structures that are more suitable for implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 This synergy may expedite the crack initiation and accelerate the fatigue crack propagation under localized corrosive effects. 13 In this regard, while extensive studies have been conducted on corrosion fatigue and its impact on the fatigue life of titanium alloys, 4,15 there is a paucity of research on porous structure implants with varying porosity gradients reported thus far. Therefore, considering the potential impact of variations in porosity gradients and corrosive solutions on the fatigue properties of alloys, and with the aim of comparing the fatigue characteristics of different gradient structures in a human body environment, the goal is to identify porous structures that are more suitable for implantation.…”
Section: Introductionmentioning
confidence: 99%
“…This synergy may expedite the crack initiation and accelerate the fatigue crack propagation under localized corrosive effects 13 . In this regard, while extensive studies have been conducted on corrosion fatigue and its impact on the fatigue life of titanium alloys, 4,15 there is a paucity of research on porous structure implants with varying porosity gradients reported thus far.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this point, additively manufactured (AM) metallic materials have drawn significant attention from both academia and industry [7]. For AM metallic materials, fatigue performance, especially in VHCF regime, has become a key factor restricting their engineering applications [6,[8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with the development of AM technology, more and more components in biomedicine, aerospace, power industry and other industrial fields are manufactured by AM, in which titanium alloys (e.g., Ti-6Al-4V) are one of the typical kinds due to its low density, high strength, good biocompatibility and excellent corrosion resistance. [4][5][6] The commonly-used AM techniques for Ti-6Al-4V parts include laser powder bed fusion (L-PBF), [7][8][9] electron beam powder bed fusion (EB-PBF), [10][11][12] directed energy deposition (DED) [13][14][15] and cold spray additive manufacturing (CSAM), 16 among which L-PBF has advantages of small dimensions and high productivity. 17 In engineering practice, L-PBF Ti-6Al-4V parts are often subjected to a long period of cyclic load during their service lives, for example, heart valve implants are subjected to about 1 Â 10 8 cycles and aircraft propel blades are subjected to about 1 Â 10 9 cycles in their entire service lives.…”
Section: Introductionmentioning
confidence: 99%